Heart Rate Monitoring System Abnormal Using a Microcontroller - Zein, Fuad; Utama, Shoffin Nahwa; Taufiqurrahman (Proceeding International Conference on Science and Engineering, 2020)
The heart is an organ of the human body that plays an important role in blood circulation and is one of the bases for knowing the physical health of every human being. The heart rate monitoring system used by health institutions is quite good but it costs a lot of usages. In the design carried out by researcher produced a tool that can detect all ages process for 60 seconds. The results after heart rate detection provide condition information and BPM (Beat Per Minute) of the heart. This tool uses a pulse sensor as a heart rate detector with a 3x4 keypad as input for age data and is displayed on a 16x2 LCD with the results of heart conditions and BPM. During testing, the researcher tested approximately 20 respondents as counted tests to put their data in a comparison table. From the results of tests that have been done are classified into two systems testing. The final result of manually testing produces a relative error percentage of 2.40%. While testing, by comparison, using a stethoscope produces a relative error percentage of 1.65%.